2017
DOI: 10.1080/09712119.2017.1299742
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding enzymatically hydrolysed yeast cell wall + yeast culture on growth performance of calf-fed Holstein steers

Abstract: One hundred and sixty-eight crossbred steers (133 ± 7 kg) were used in a 336-d experiment to evaluate the effects of enzymatically hydrolysed yeast cell wall plus yeast culture (EHY) supplementation on growth performance and carcass characteristics. Treatments consisted of steam-flaked corn-based diet supplemented with 0, 195, 390 or 585 mg/kg EHY. Supplemental EHY enhanced overall (336-d) dry matter intake (DMI, P < .01), averagde daily gain (ADG, P = .04), and final carcass weight (P = .04). Responses were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
(19 reference statements)
2
14
0
Order By: Relevance
“…There were no appreciable differences detected for performance-based dietary NE m ( P = 0.70) or NE g ( P = 0.59) in the present study. This is similar to what others have reported in response to the use of a yeast culture-based product in shipping-stressed calves and growing–finishing Holstein steers ( Zinn et al, 1999 ; Salinas-Chavira et al, 2018 ). Likewise, there were no differences detected between treatments for the ratio of observed to expected dietary NE m ( P = 0.70) or the ratio of observed to expected dietary NE g ( P = 0.59), which is similar to what others have demonstrated in a transit-stressed calf model, as well as growing and finishing Holstein steers ( Zinn et al, 1999 ; Salinas-Chavira et al, 2018 ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…There were no appreciable differences detected for performance-based dietary NE m ( P = 0.70) or NE g ( P = 0.59) in the present study. This is similar to what others have reported in response to the use of a yeast culture-based product in shipping-stressed calves and growing–finishing Holstein steers ( Zinn et al, 1999 ; Salinas-Chavira et al, 2018 ). Likewise, there were no differences detected between treatments for the ratio of observed to expected dietary NE m ( P = 0.70) or the ratio of observed to expected dietary NE g ( P = 0.59), which is similar to what others have demonstrated in a transit-stressed calf model, as well as growing and finishing Holstein steers ( Zinn et al, 1999 ; Salinas-Chavira et al, 2018 ).…”
Section: Resultssupporting
confidence: 90%
“…When a live yeast Saccharomyces cerevisiae boulardii CNCM I-1079 was fed to high-risk receiving heifers, improvements in growth performance during the initial 45 d on feed, as well as improved health outcomes, were noted ( Theurer et al, 2019 ). When an enzymatically hydrolyzed yeast was fed to growing Holstein steers, a 3.4 % increase in ADG and a 3.4 % increase in DMI was noted and steers exhibited similar feed efficiency ( Salinas-Chavira et al, 2018 ). However, when enzymatically hydrolyzed yeast was fed to crossbred beef steers, a 9% increase in ADG was observed during the finishing phase of production ( Salinas-Chavira et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, increased ADG of Celmanax-supplemented ruminants has been associated with increased DM intake (Ponce et al, 2012;Nde et al, 2014). Supplementing S. cerevisiae-derived products to cattle may improve ruminal fiber degradation and microbial protein synthesis (Miller-Webster et al, 2002;Salinas-Chavira et al, 2015;Salinas-Chavira et al, 2017), which in turn regulate DM intake in ruminants (Allen, 1996). Accordingly, Ponce et al (2012) reported greater concentrate intake, but similar hay intake and overall feed efficiency, in Celmanax-supplemented compared with non-supplemented heifers during feedlot receiving.…”
Section: Discussionmentioning
confidence: 99%
“…Sánchez-Mendoza et al (2015) observed that a chromium-enriched YCW increased ADG and tended to increase DMI during the first 112 d of a trial, but not the last 100 d or overall compared with no YCW. Holstein steers supplemented with 0, 195, 390, or 585 mg/kg diet DM of enzymatically hydrolyzed YCW + yeast culture for 336 d had increased overall DMI, ADG, and final carcass weight, with maximal effects observed at 195 mg/kg YCW (Salinas-Chavira et al, 2017). The inclusion of YCW for the final 55 d in steers fed zilpaterol hydrochloride resulted in increased carcass adjusted final BW, ADG, and G:F from day 21 to 55, but there were no other differences in performance or carcass characteristics (Aragon et al, 2016).…”
Section: Performancementioning
confidence: 99%